Akuntabilitas Keuangan Daerah Ditinjau dari Pengendalian Intern dan Kompetensi Aparatur serta Dampaknya terhadap Akuntabilitas Kinerja Instansi Pemerintah - Faturahman, F (AKTSAR: Jurnal Akuntansi Syariah, 2020)
The purpose of this study was to analyze the effect of internal control and government employee competencies on regional financial accountability, and its impact on the accountability of the performance of government agencies in the city of Jambi. The type of data used is primary and secondary data. Population and sample are all government units (SKPD) in Jambi City which have government performance accountability report (LAKIP) value. Data were analyzed using path analysis. The results showed that Internal Control and Government Employee Competence significantly influence Regional Financial Accountability. Furthermore, Internal Control has a greater indirect effect when compared to the direct effect on the Accountability of Government Units Performance. While Employee Competence has a greater direct effect when compared to the indirect effect on the Accountability of Government Institution Performance.